Edukasi Range Of Motion Aktif Kaki dengan Audiovisual pada Penderita Diabetes Melitus Tipe II: Literature Review - Arinda Putri Hapsari; Putrono Putrono; Nina Indriyawati (JENDELA NURSING JOURNAL, 2020)
Background: The number of death cause type II diabetic and the low of knowledge level in pyhsical activity is still high.Purpose: This literature review discusses about the usage of audiovisual as media for education to increase the level of type II diabetic accusative’s knowledge and skill in active lower ROM.Methods: This research used 9 articles from over 96 international and national journals published between 2015-2019, five databases were used to facilitate the literature research (Pubmed, Elsevier, Google Scholar, dan SINTA). Inclusion and exclusion criteria for the literature search were applied and PRISMA guidelines followed. The inclusion criteria of studies using audiovisual, type II diabetic, and active lower ROM. The exclusion criteria of this research are research that used media except audiovisual.Results: The result from this literature review is from 9 articles show that audiovisual is a good media for education especially education to increase the level of Type II diabetic accusative’s knowledge and skill in active lower ROM.Conclusion: Audiovisual can be used as media for education to increase the level of type II diabetic accusative’s knowledge and skill in lower active ROM.